Pulp Production from Pineapple Leaf Waste for Sustainable Paper Manufacturing - Md. Didarul Alam, Chowdhury; Ektiar, Uddin; Muhammad Misbah, Uddin; Rehan, Hasnain; S. M. Mehedi, Afnan Rejve; Md Shiman, Rusdi; Rezaur, Rahman; Muneera S. M., Al-Saleem; Jehan Y., Al-Humaidi; Mohammed M., Rahman (NC State University, 2025)
The agricultural sector generates considerable amounts of waste annually, particularly during harvest periods. This study explored the potential of pineapple (Ananas comosus Merr.) leaves, a cellulose-rich byproduct of the pineapple industry, as a sustainable raw material for paper production. Mechanical strength, renewability, and cost-effectiveness make pineapple leaves a promising alternative for ecofriendly papermaking. The research focused on analyzing the chemical composition of the leaves, optimizing the pulping process, and evaluating the physical properties of the resulting paper. Utilizing TAPPI test methods, the chemical analysis revealed high concentrations of holocellulose (82.6%), alpha-cellulose (69.7%), and hemicellulose (12.9%), along with relatively low levels of solvent extractives (14.7%) and ash content (4.9%). The physical attributes of the produced paper include a tensile index of 50.1